Corporate Talent Detection and Development - Richez, Yves (Wiley-ISTE, 2018)
Talent is not a matter of status, nor a sub-component of personality, nor a commodity that can be quantified or measured. This book consists of two parts. The first offers a fertile resource (epistemological and theoretical) to consider the notion of talent, as well as notions of potential, intelligence and business skills. The second part, in turn, investigates ten major families of talents (or "Natural Operating Modes"). From Marie Curie to Walt Disney, Hans Zimmer, Gabrielle Chanel and Claude Lévi-Strauss, the illustrations and examples are intended to be precise and demonstrative. Skills relating to observation, evaluation and elucidation are developed in detail and complemented with concrete examples. Both managers and employees can use this book to acquire the solid bases required to potentiate and develop their talents within their respective company and beyond.